Cultural Integration and Its Discontents - KURAN, TIMUR; SANDHOLM, WILLIAM H. (Review of Economic Studies, 2008)
A community's culture is defined by the preferences and equilibrium behaviours of its members. Contacts among communities alter individual cultures through two interrelated mechanisms: behavioural adaptations driven by pay-offs to coordination, and preference changes shaped by socialization and self-persuasion. This paper explores the workings of these mechanisms through a model of cultural integration in which preferences and behaviours vary continuously. It identifies a broad set of conditions under which cross-cultural contacts promote cultural hybridization. The analysis suggests that policies to support social integration serve to homogenize preferences across communities, thereby undermining a key objective of multiculturalism. Yielding fresh insights into strategies pursued to influence cultural trends, it also shows that communities benefit from having other communities adjust their behaviours.